2016
DOI: 10.17073/0368-0797-2016-5-293-299
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Dust Formation During Arc Melting of Zinc-Coated Steel

Abstract: Аннотация. Изучен процесс образования пыли при плазменно-дуговом нагреве оцинкованной стали в атмосфере аргона при силе тока от 170 -190 А, расходе аргона 0,06 м 3 /ч, давлении в камере печи 0,1 МПа. Установлено, что цинк практически полностью испаряется в течение первых 30 с плавки. Структура уловленной цинксодержащей пыли неоднородна: наблюдаются частицы различных форм (сфери-ческие, игольчатые, шаровидные пленчатые), размеров и состава. Проведен анализ элементного состава отдельных частиц образующейся пыли … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The works [1][2][3][4][5][6][7][8][9][10] describe a method of extracting zinc from the BF and EAF dust using the Waelz process. In [12] and [13], it was shown that zinc in the dust of metallurgical aggregates can be presented not in pure oxide form, but in the solid solutions form of complex iron-silicate compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The works [1][2][3][4][5][6][7][8][9][10] describe a method of extracting zinc from the BF and EAF dust using the Waelz process. In [12] and [13], it was shown that zinc in the dust of metallurgical aggregates can be presented not in pure oxide form, but in the solid solutions form of complex iron-silicate compounds.…”
Section: Methodsmentioning
confidence: 99%